Samarium Diiodide Mediated Coupling of 2‐Pyridylsulfonyl Furanosides with Aldehydes and Ketones: A General Synthesis of C‐Furanosides12. Issue 12 (6th March 2015) - Wang, Jin; Gasc, Fabien; Prandi, Jacques
Abstract: Diiodosamarium‐mediated coupling of anomeric 2‐pyridyl sulfones derived from furanosides with carbonyl compounds, aldehydes, and ketones gave α‐hydroxylated 2, 5‐ trans ‐dialkylated tetrahydrofurans with good yields and useful stereoselectivities. The main control element of the reaction is the substituent on the 4‐position or the starting furanosyl sulfone. C ‐Furanosides ofD ‐arabinose and ofD ‐ribose were obtained from sulfones prepared from the corresponding furanosides. Finally, a di‐ C ‐arabinofuranoside, a C ‐disaccharide analogue of a major motif of the arabinogalactan from the mycobacterial cell wall, was prepared. Abstract : C ‐Furanosides were obtained from the diiodosamarium‐mediated coupling of anomeric 2‐pyridyl sulfones derived fromD ‐arabinose andD ‐ribose with aldehydes and ketones. Useful selectivities were observed and products with a trans relationship between the two carbon substituents on the tetrahydrofuran system were obtained.